FENOMENA TRENDING TOPIC DI TWITTER: ANALISIS WACANA TWIT #SAVEHAJILULUNG - Juditha, Christiany (Jurnal Penelitian Komunikasi dan Pembangunan, 2015)
Social media Twitter abstraction of the most actively used in Indonesia. Users often involved in the topics being discussed in cyberspace. No wonder if the Twitter trending topic dominated by the topic of Indonesian origin. The phenomenon that gave make to freedom of speech in social media also raises a problem where if there is a specific topic that is not liked then, netizens busy to bully certain parties, one of which in the case of Haji Lulung. The research objective is to get an overview of discourse analysis of tweet #SaveHajiLulung who became a trending topic on Twitter. This study uses content analysis of discourse van Dijk of the structure macro, super structure and microstructure. The study concluded that the most prominent theme is the figure of Haji Lulung in negatively (satire) by netizens. This scheme netizen opinion abreast case of issues every day. There is a process whereby discourse Lulung was first rolled in the media, which was, then a lot of netizens response. The process of growing into a discourse not just posting tweets and retweets, but is followed by meme (funny pictures) about Lulung. Meaning that emphasized mostly contains elements of parody about Lulung, tend to hyperbole (exaggerate) and the reps alteration (repeat).